Mesenchymal stem cell therapy in the treatment of osteoarthritis: reparative pathways, safety and efficacy – a review. Issue 1 (December 2016) - Freitag, Julien; Bates, Dan; Boyd, Richard; Shah, Kiran; Barnard, Adele; Huguenin, Leesa; Tenen, Abi
Abstract Osteoarthritis is a leading cause of pain and disability across the world. With an aging population its prevalence is likely to further increase. Current accepted medical treatment strategies are aimed at symptom control rather than disease modification. Surgical options including joint replacement are not without possible significant complications. A growing interest in the area of regenerative medicine, led by an improved understanding of the role of mesenchymal stem cells in tissue homeostasis and repair, has seen recent focused efforts to explore the potential of stem cell therapies in the active management of symptomatic osteoarthritis. Encouragingly, results of pre-clinical and clinical trials have provided initial evidence of efficacy and indicated safety in the therapeutic use of mesenchymal stem cell therapies for the treatment of knee osteoarthritis. This paper explores the pathogenesis of osteoarthritis and how mesenchymal stem cells may play a role in future management strategies of this disabling condition.